Diffuse Liver Metastasis From Nasopharyngeal Carcinoma Found by 18F-FDG PET/CT Scans. (October 2018) - Zhang, Xin-Yun; Chen, Xiao-Yue; Zhang, Guo-Qiang; Luo, Quan-Yong
Abstract : Abstract: A 54-year-old man with a history of nasopharyngeal carcinoma was treated with TPF (docetaxel + cisplatin + 5-fluorouracil) neoadjuvant chemotherapy, presented with clinical features of acute hepatic failure. 18 F-FDG PET/CT revealed diffuse hepatic radioactivity uptake without pathological radioactivity elsewhere in the body and similar to superscan by bone scan. Increased focal uptake of FDG was more commonly seen in nasopharyngeal carcinoma with metastatic involvement of the liver. This unusual liver superscan indicated that patients with nasopharyngeal carcinoma may show diffuse hepatic involvement by cancer cells and inspired our interests.